ENVIRONMENTAL EDUCATION IN PRE-SCHOOL AND PRIMARY CLASS CHILDREN IS THE GOAL OF EDUCATION (Web of Teachers: Inderscience Research, 2024)
In this article, the main goal of environmental education is to form a conscious attitude to the environment and its problems in preschool children, as well as the knowledge, skills and abilities to find optimal solutions to them. In this sense, the article analyzes the purpose of environmental education in preschool educational organizations.